Unusual phonon mode behaviour in zinc‐blende BN/GaN superlattices. Issue 4 (23rd January 2015) - Talwar, Devki N.; Zhou, Andrew F.; Yang, Tzuen‐Rong
Abstract: Comprehensive calculations of the long‐wavelength optical phonons are reported for zinc‐blende BN films by exploiting a linear response theory to simulate far‐infrared reflectivity and transmission spectra at oblique incidence. A rigid‐ion‐model is used to study the lattice dynamics of the unconventional BN/GaN short‐period superlattices (SLs). Besides empathizing, the anisotropic mode behaviour of optical phonons, the study has offered evidence of acoustic‐mode anti‐crossing, mini‐gap formation, confinement, as well as BN‐like modes falling between the gap regions separating the optical phonons of the two bulk (BN, GaN) semiconductor materials. A bond‐polarizability approach within the second‐nearest‐neighbour linear‐chain model is also employed to visualize the Raman intensity profiles of the short‐period BN/GaN SLs, revealing major trends of the phonon characteristics noted in many conventional SLs, while eliciting some interesting contrasts. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)